Comprehensive risk assessment of urban floods based on flood simulation and socio-economic vulnerability - Ma, Bingyan; Guo, Jing; Chen, Pengyu; Zhang, Leilei; Wang, Huiliang; Zhou, Yihong; Sun, Boyu (Frontiers in Earth Science, 2025)
Urban flooding has become a global problem, seriously threatening the healthy development of cities and the safety of people’s lives and property. Urban flood risk assessment can effectively identify potential hazardous areas and provide a basis for the development of targeted disaster prevention and mitigation strategies. However, the current urban flood risk assessment research is mainly based on the flood inundation or indicator evaluation system, the lack of inundation characteristic and hazard-bearing body socio-economic attributes of the comprehensive consideration, resulting in the assessment results and the actual flood risk there is a certain deviation. Therefore, this study integrated urban hydrological and hydrodynamic simulation technology and Fuzzy Matter-Element (FME) theory, proposed a comprehensive flood risk assessment method that takes flood inundation and socio-economic vulnerability into account, and quantitatively evaluates the flooding risk of Zhengzhou City under different rainfall return periods. The results indicate that low-risk zones are primarily located in the peripheral and fringe regions of Zhengzhou, whereas high and very-high risk zones are predominantly situated in the central urban area, particularly in the western Jinshui District, northeastern Erqi District, and northern Guancheng District. These areas are the old urban areas of Zhengzhou City which were constructed earlier, and are characterized by low drainage system construction standards, aging pipe networks, dense population and road networks, and high economic value. The results contribute methodological guidance and decision-making reference for urban flood management and control.